Sea as an Element and a Space of Confrontation between Nature and Culture. Damir Miloš’s Ecopoetics in Kornatske priče and Meke ulice - Szperlik, Ewa (Poznańskie Studia Slawistyczne, 2022)
The article attempts to present selected prose works by Damir Miloš as an example of Croatian maritime literature and ecological writing. In the posthumanist view, the symbiosis of man and nature constitutes a postpastoral attempt to return to Arcadia. In Miloš’s prose, ecopoetics is manifested in J. F. Lyotard’s idea of “house-building” ( oikon and poesis ), which is currently also discussed by other researchers, in the harmony of the human and the world of nature, as well as in the perspective of pansociologism, according to which “everything is society,” and all existence means “entering into interactions,” and, lastly, in the optics of Bruno Latour’s hyperhumanism. The element of the sea ( its flora and fauna) in an ecocritical approach is characterised by liquidity, ambiguity as well as transgression and liminality ( between the world of nature and culture ). In addition to its causative elements, it can also communicate ( non-anthroponormative languages, post-koiné ).